Sudden change of pedagogy in education driven by COVID-19: Perspectives and evaluation from a developing country. (December 2020) - Oyedotun, Temitayo Deborah
Abstract: The COVID-19 pandemic has forced sudden transformation in many sectors of the global community, turning the world upside down. Everything has been impacted, not excluding the education sector, which has experienced some unforeseen changes in many parts of the world. The sudden transition to online pedagogy as a result of COVID-19 in developing countries has exposed some inequalities and challenges, as well as benefits. These challenges and inequalities have now become the new realities in the educational sector of developing countries. Suggestions are provided here so that the challenges presented by the new approach can be mitigated while we come to terms with the disruptions introduced by COVID-19 to our education sector.